Saints et Sainteté dans le mormonisme de Joseph Smith et celui de l'Église de Jésus-Christ des Saints des Derniers Jours - Chrystal Vanel (Conserveries Mémorielles)
Since the beginning of Mormonism in the 19th century, its followers have considered themselves as « Latter Day Saints », having made a covenant with God like puritans before them. Mormon saintliness was then lived out through sanctified communities that were socially, culturally and even sometimes politically separated from the world. As the practice of polygamy came to an end in 1890/1904, "political Mormonism" no longer existed: the "Saint" now established boundaries between himself and the rest of the world on an individual basis through proscriptions and obligations. But to the saintliness already present in Puritanism, Mormonism adds deification: the sanctified Mormon can go into a Temple whose rituals will lead him to godliness. Thus, Mormonism takes the idea of saintliness even further, a word often considered to be a divine attribute.